Digital Audit: Technological Innovation and Its Impact on Audit Quality - Stephanie Olivia br. Sihaloho; Cicilya Evangelista Yunani Purba; Iskandar Muda (CV. Ulil Albab Corp, 2025)
In essence, human beings are social creatures who continuously develop over time, producing various innovations that emerge from creative ideas. Within this scope, we analyze the adoption of digital audit technologies using the Innovation Diffusion Theory, identifying key factors that influence their acceptance and integration into audit quality. This effort aims to optimize the problem-solving process as a sustainable solution for increasing organizational performance and accountability. This study employs a Systematic Literature Review (SLR) to investigate the theme and confirm validity and reliability of the findings. The importance of auditors in justify professional competencies, adopting technological capabilities, and engaging in continuous development to remain relevant in a digital environment. This manuscript explains the progression of advanced technologies and their critical role in reshaping modern auditing practices. The study’s results reveal how the perceived attributes of innovation namely relative advantage, compatibility, trialability, complexity, and observability contribute to variations in audit quality and organizational trust. Further investigations are recommended to explore the ethical dimensions associated with automation in auditing, particularly in areas such as transparency, accountability, and independence. This study explores a highly relevant issue by analyzing how auditing practices are evolving in the context of digital transformation. Digital audit represents a new way of conducting assurance engagements using advanced technologies like AI, data analytics, and blockchain. Unlike traditional audits, it allows faster, automated, and data-driven processes. This focus recognizes the quickly changing business environment and the increasing significance of technological innovation in contemporary audit procedures.